MAZHAB SARTONO DAN SEJARAH SOSIOLOGIS - Mochamad Syawie (Politeknik Kesejahteraan Sosial, 2005)
(The Sartono School and Sociological Histpry) - Today, social phenomenon is growing, to be more complex and intertwined. Multidicilpline approach is the logic method to meet the complex and multidimentional phenomenon. Monodicipline approach become useles in the social study context, because the result only able to write in narrative model describedon a narration paper. The narrative model only describe a narration without pretention relative with how and why it can be. The ideal type is a construct, something that be developed in researcher mind. The construct is an instrument to identify the concrete social symptoms. The professional who have linked with this area are sociologist and historian, as their analysis using both social and historical science. The impact of the symptoms rise the new subdicipline nomely historical sociology or sociological history. This indicate that there is magnify growth in the social science. The explanation shown above between social and historical science is intertwined, so the reproachement efforts need to be done continueing.